A low-carbohydrate diet induces hepatic insulin resistance and metabolic associated fatty liver disease in mice - Fen Long; Memoona R. Bhatti; Alexandra Kellenberger; Wenfei Sun; Salvatore Modica; Marcus Höring; Gerhard Liebisch; Jean-Philippe Krieger; Christian Wolfrum; Tenagne D. Challa (Molecular Metabolism, 2023)
Objectives: Metabolic-associated fatty liver disease (MAFLD) is the most common chronic liver disease that can range from hepatic steatosis to non-alcoholic steatohepatitis (NASH), which can lead to fibrosis and cirrhosis. Recently, ketogenic diet (KD), a low carbohydrate diet, gained popularity as a weight-loss approach, although it has been reported to induce hepatic insulin resistance and steatosis in animal model systems via an undefined mechanism. Herein, we investigated the KD metabolic benefits and its contribution to the pathogenesis of NASH. Methods: Using metabolic, biochemical and omics approaches, we identified the effects of a KD on NASH and investigated the mechanisms by which KD induces hepatic insulin resistance and steatosis. Results: We demonstrate that KD can induce fibrosis and NASH regardless of body weight loss compared to high-fat diet (HFD) fed mice at thermoneutrality. At ambient temperature (23 °C), KD-fed mice develop a severe hepatic injury, inflammation, and steatosis. In addition, KD increases liver cholesterol, IL-6, and p-JNK and aggravates diet induced-glucose intolerance and hepatic insulin resistance compared to HFD. Pharmacological inhibition of IL-6 and JNK reverses KD-induced glucose intolerance, and hepatic steatosis and restores insulin sensitivity. Conclusions: Our studies uncover a new mechanism for KD-induced hepatic insulin resistance and NASH potentially via IL-6-JNK signaling and provide a new NASH mouse model.